Nanosponges –A Promising Novel Drug Delivery System - Pandey, Parijat; Purohit, Deepika; Dureja, Harish (Recent Patents on Nanotechnology, 2018)
Background: Pharmacokinetic issues and poor solubility in water are the most important concerns of numerous recently developed chemical entities. Objective: The drugs which are poorly soluble in water demonstrate numerous formulating troubles in conventional dosage forms and the low bio-availability is the critical problem linked with it. A nanosponge is an emerging technology which can overcome these problems and precisely control the release rates of controlled drug delivery. Method: Nanosponges are tiny mesh-like structures with a size less than 1μm. Due to their porous structure and small size; they can easily bind to drugs which are poorly-soluble leading to better bioavailability and solubility of such drugs. A broad range of drugs including both hydrophilic and lipophilic can be easily loaded into nanosponges. Results: These minute sponges can circulate until they reach the definite target site, attach themselves to the surface and initiate the discharge of drugs in a predictable and controlled way. Nanosponges are solid in character and can be developed in various dosage forms such as parenteral, topical, oral or inhalational. Nanosponge drug delivery system has been developed as one of the most capable aspects in the field of pharmaceuticals. Conclusion: In this review, an attempt has been made to highlight the advantages, characteristics, application, methods of preparation and characterization of nanosponges along with the recent patents on nanosponges.
Keywords: controlled release